Arachidonic acid metabolites and enzyme transcripts in asthma are altered by cigarette smoking. Issue 4 (26th February 2014) - Thomson, N. C.; Chaudhuri, R.; Spears, M.; Messow, C. M.; Jelinsky, S.; Miele, G.; Nocka, K.; Takahashi, E.; Hilmi, O. J.; Shepherd, M. C.; Miller, D. K.; McSharry, C.
Abstract Background Arachidonic acid metabolites are implicated in the pathogenesis of asthma although only limited information is available on the impact of current smoking history on these metabolites. The aim of the study was to examine the effect of smoking status on urinary, sputum, and plasma eicosanoid concentrations and relevant enzyme transcripts in asthma. Methods In 108 smokers and never smokers with asthma and 45 healthy controls [smokers and never smokers], we measured urinary tetranor prostaglandin (PG)D2 (PGDM) and leukotriene (LT)E4, induced sputum fluid LTB4, LTE4, PGD2, and PGE2, plasma secretory phospholipase A2 (sPLA2), and 11β prostaglandin F2α (11βPGF2α), and, in a subgroup with severe asthma, airway leukocyte and epithelial cell mRNA expression levels of arachidonic acid metabolic enzymes. Results Smokers with asthma had higher urinary LTE4; 83 (59, 130) vs 59 (40, 90) pg/mg creatinine, P = 0.008, and PGDM; 60 (35, 100) vs 41 (28, 59) ng/mg creatinine, P = 0.012 concentrations, respectively, and lower sputum PGE2 concentrations 80 (46, 157) vs 192 (91, 301) pg/ml, P = 0.001 than never smokers with asthma. Sputum LTB4(P = 0.013), and plasma 11βPGF2α(P = 0.032), concentrations, respectively, were increased in smokers with asthma compared with healthy smokers. Asthma‐specific and smoking‐related increases (>1.5‐fold expression) in arachidonate 15‐lipoxygenase and gamma‐glutamyltransferase transcripts were demonstrated. Conclusions Several arachidonic acid metabolites and enzyme transcripts involving both lipoxygenase and cyclooxygenase pathways are increased in smokers with asthma and differ from never smokers with asthma. Possibly targeting specific lipoxygenase and cyclooxygenase pathways that are activated by asthma and cigarette smoking may optimize therapeutic responses.